Pretty simple cocktails : margaritas, mocktails, spritzes, and more for every mood and occasion - McIntosh, Julianna (Clarkson Potter/Publishers, 2024)
"Indulge in 65 deliciously dreamy cocktails and mocktails from the social media influencer behind Join Jules! A friendly, whimsical approach to mixology from Julianna McIntosh, the self-taught cocktail pro behind the join jules social media platforms! Perfect for anyone who wants a well-balanced cocktail that's as chic as it is easy to shake, Pretty Simple Cocktails breaks down the basics of cocktail making from bar equipment to mixing syrups. In addition to recipes divided by occasion and seasonality, Julianna offers plenty of smart tips for building and maintaining a home bar including her list of must-have equipment (with substitution options), a cocktail glass primer, a how-to on picture-perfect garnishes (dehydrated citrus! brûléed fruit!), and a specialty liqueur index so every bottle you buy gets used again and again. Whether you're hosting a swanky cocktail party or batching drinks to bring to the beach, Pretty Simple Cocktails has you covered. Pretty Simple Cocktails delivers a rich variety of impressive recipes, inspiration, and guidance for making your own cocktails such as: Relaxed Refreshers: Tequila Mango Refresher, Low-ABV Spicy Fizz; Spritz is a State of Mind: Sparkling Cosmo Spritz, Rosé All Day Spritz; A Margarita For Every Mood: Pineapple Mezcal Margarita, Aperol Strawberry Coconut Margarita; Start the Party on a High Note: Olive Oil Martini, Stone Fruit Whiskey Sour; Drinks for Cozy Occasions: Tiramisu Espresso-tini, Homemade Citrus-Cello; Booze-Free Beauties: Watermelon Smash, Garden Refresher Punch; Syrups (to be mixed with alcohol or with n/a mixers): Passionfruit Syrup, Prosecco Syrup. Served up with grace and flair, Julianna's dazzling collection of thirst-quenching recipes will impress with its delightful voice and generous salt rims"--